2012
DOI: 10.1186/1472-6963-12-449
|View full text |Cite
|
Sign up to set email alerts
|

The effect of community-based health management on the health of the elderly: a randomized controlled trial from China

Abstract: BackgroundAn aging population poses significant challenges to health care in China. Health management has been implemented to reduce the costs of care, raise health service utilization, increase health knowledge and improve quality of life. Several studies have tried to verify the effectiveness of health management in achieving these goals worldwide. However, there have been insufficient randomized control trials (RCTs) to draw reliable conclusions. The few small-scale studies conducted in China include mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 18 publications
2
60
0
Order By: Relevance
“…Within the group, older people could reduce isolation and loneliness because they began to connect with others who have experience of aging [ 27 ]. The findings of this study are also consistent with the study results reported by Chao and colleagues [ 28 ] which showed that 1163 persons in a health management program based community showed improvement in physical health. Analysis from Whittle et al [ 10 ] found that through peer-delivered self-management support, health conditions such as hypertension improved, with a significant decrease in systolic blood pressure.…”
Section: Discussionsupporting
confidence: 93%
“…Within the group, older people could reduce isolation and loneliness because they began to connect with others who have experience of aging [ 27 ]. The findings of this study are also consistent with the study results reported by Chao and colleagues [ 28 ] which showed that 1163 persons in a health management program based community showed improvement in physical health. Analysis from Whittle et al [ 10 ] found that through peer-delivered self-management support, health conditions such as hypertension improved, with a significant decrease in systolic blood pressure.…”
Section: Discussionsupporting
confidence: 93%
“…A number of barriers may prevent senior patients with hypertension from engaging in physical activities at the community level [ 13 , 14 ]. Hypertensive patients are often older in age and lower in self-confidence to engage in physical activity [ 15 , 16 ]; these patients are also lack of adequate societal and familial supports [ 15 , 16 ] to maintain recommended activity levels [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, as a major model of primary care, community health service centers (CHSCs) play an increasingly important role in the prevention and control of non-communicable diseases [ 14 ]. All the CHSCs are operated and funded by the Government and they are responsible for providing necessary healthcare services to local residents.…”
Section: Introductionmentioning
confidence: 99%